(untitled) (Research, Society and Development, 2020)
Objective: To estimate the frequency of causes of ineptitude among candidates for blood donation in the hemotherapy service of a university hospital in the State of Rio de Janeiro. Method: This is a descriptive exploratory cross-sectional field study with quantitative approach and convenience sampling, conducted from November 2018 to March 2020. Sociodemographic and clinical-laboratory data were obtained through the application of a pre-structured questionnaire and consultation of the hemotherapy system used in the service (Hemote Plus system®). The sample size considered the mean number of donors in the last 5 years and a sampling error of 5%. Pearson’s chi-square test was applied to bivariate analyses, considering a significance level of 5%. Results: Of the 400 respondents, 25 (6.3%) multiple partnership in the last 12 months and 42 (10.5%) have never used a condom. The general frequency of ineptitude observed was 77 cases (19.25%), anemia being the most frequent (18.2%), followed by serological ineptitude (16.9%), and 11.7% were related to risky sexual behavior. Repeat donors have greater motivation to voluntarily donate 178 (81,3%) and tend to rely fully on test results 260 (73.7%) in relation to first-time donors. Conclusion: The prevalence of ineptitude by positive serologies and risky sexual behavior confirms the need for educational practices aimed at specific groups, aiming to minimize the disposal of blood bags. Encouraging donor loyalty can be a powerful tool for ensuring the quality of the given blood.